Analisis Pemahaman Masyarakat Lokal terhadap Regulasi Pengelolaan Wisata Pemandian Air Panas Aek Milas Sosopan (Lembaga Pengembangan Kinerja Dosen, 2025)
Aek Milas Sosopan Hot Springs is one of the local tourist destinations with great potential in attracting tourists. However, less than optimal tourism management is caused by the lack of understanding of local communities regarding tourism management regulations and environmental management. This study aims to determine the understanding of local communities regarding the management regulations of Aek Milas Sosopan Hot Springs as a tourist destination and to determine environmental management in Aek Milas Sosopam Hot Springs. This study uses the Normative-Empirical legal research method with a qualitative approach. Data were obtained through interviews, observations, and documentation from local communities involved in tourism management. The data analysis technique used is the Miles and Huberman interactive model, which consists of data reduction, data presentation, and verification or drawing conclusions. The results of the study indicate that local communities' understanding of tourism management regulations is still very low, and environmental management is not yet structured and sustainable. The researcher suggests that the local government immediately draft written regulations, conduct socialization, and form a formal management structure, and provide technical training and education to the community. Local communities are expected to be more proactive in maintaining environmental cleanliness and sustainability and be open to training and cooperation with the government. This research is expected to be a reference for the development of more effective and sustainable tourism management at the local level.